Subjective experience and visual attention to a historic building: A real-world eye-tracking study - De la Fuente Suárez, Luis Alfonso (2020)
The objective of this exploratory study is to discover the relations between visual attention to an architectural work and the subjective experiences produced during its observation. A subjective experience with a building is the specific manner in which an architectural element or the building as a whole are presented to a person. The qualities of the element as how they are perceived and the inner world of the observer are both considered in this subjective experience. The aims of this study are to describe the experience that a building generates in people, pinpoint what has attracted the participant’s attention during each view of the building in an itinerary; and understand which aspects of this selected case study have made it an object of attention. An eye-tracking study was carried out using a portable eye tracker. This tool allowed the participants to walk freely around the exterior of a historic train station in the city of Monterrey, Mexico. Two groups of participants, with routes starting from opposite sides of the building, contemplated it while using the eye tracker. Eye tracking allowed for the identification of the architectural elements that were objects of attention, the lengths of observation, and the points of view from which the elements were observed. Other data collection techniques, such as the think-aloud protocol and a special type of survey, were used to deeply understand the experiences that accompanied the visual exploration of the historic building. Results suggest that the participants observed the different architectural elements for a time that was neither influenced by the route used to explore the building nor the point where that route was initiated. The architectural elements identified as examples of high-quality architecture and perceived as aesthetically pleasing by the participants during the itinerary were observed for longer times